From Profit To Falah; Shifting Value Paradigms in Digital Economy from the Perspective of Islamic Economic Philosophy - Resty Amelia; Bunga Cinta Cahaya; Zaharani Tirta; Havis Aravik (Jurnal Studi Islam Indonesia (JSII), 2026)
The development of the digital economy has driven an increasingly profit-oriented orientation in economic activity, often neglecting ethical values, justice, and social welfare. This situation has given rise to fundamental issues related to social inequality, resource exploitation, and the blurring of moral values in modern economic practices. This article aims to analyze the shift in the value paradigm from a profit-oriented orientation to the concept of falah in the digital economy, based on the perspective of Islamic economic philosophy. The research method used is library research with a qualitative-descriptive approach, through an analysis of classical and contemporary literature relevant to Islamic economics, the philosophy of values, and the digital economy. The results of the study indicate that Islamic economics offers a more holistic value paradigm, where falah is understood as well-being in this world and the hereafter, encompassing material, spiritual, and social dimensions. The application of the values of monotheism, justice, balance, and moral responsibility in the digital economy has the potential to direct economic activity not only toward efficiency and profit, but also toward sustainability and the welfare of the community. Thus, the paradigm shift from profit to falah is a crucial foundation for building an ethical and just digital economy in accordance with Islamic economic principles